Analysis on the mediating effect and regulating impact of carbon finance on quality-focused economy advancement - Jiang, Lili; Niu, Huawei; Ru, Yufan; Tong, Aihua; Wang, Yifeng (Frontiers in Environmental Science, 2023)
This article uses the entropy weight method to calculate China's economic high-quality development index and carbon finance development index from 2000 to 2020.Additionally, it conducts empirical examinations to scrutinize impacts of carbon finance regarding quality-focused development of China's economy through dynamic spatial models. The findings reveal that the advancement of carbon finance substantively promotes the quality-focused economy advancement through enhancing the overall factor productivity, thereby establishing a mediating effect. Concurrently, the allocation of resources in green fiscal expenditure assumes a moderating effect, subsequently amplifying the promoting effect of carbon finance regarding quality-focused economy advancement. Consequently, it is recommended that a robust financial milieu be established, energy efficiency be enhanced, scientific and technological progress be bolstered, total factor productivity be further augmented, and the expenditure on green conservation be escalated. These measures will effectively stimulate the quality-focused development of China's economy.